MAGNETIC PROPERTIES AND MAGNETIC FABRICS OF PLEISTOCENE LOESS/PALAEOSOL DEPOSITS ALONG WEST-CENTRAL SIBERIAN TRANSECT AND THEIR PALAEOCLIMATIC IMPLICATIONS - Matasova G.G.; Kazansky A.Yu. (My University, 2004)
Rock-magnetic properties, in particular anisotropy of magnetic susceptibility (AMS) were investigated in detail for eight sections transecting southwestern and central parts of Siberia. The results obtained indicate that magnetic properties and magnetic fabrics of loess/ palaeosol deposits in western and southwestern Siberia depend on superposition of two different mechanisms namely a pedogenic mechanism proposed for Chinese loess and a wind-vigour mechanism for Alaskan loess. The wind-vigour mechanism is predominant in loess deposits and this allows palaeowind directions during glacial periods to be determined. In palaeosols, the balance between both models strongly depends on the geographical position of the section and thus reflects the palaeoclimate. In western Siberia, palaeosols corresponding to OIS 3 have sedimentary magnetic fabric, while the magnetic fabric of palaeosols corresponding to OIS 5 is completely reworked by pedogenesis. Such differences indicate a warmer climate during OIS 5. In central Siberia, separated from the west by the Kuznetsk Ala-Tau mountain ridge, the magnetic properties and AMS of loess/palaeosol sequences agree with 'Alaskan' type of loess, suggesting a colder and windier climate during the Late Pleistocene. Therefore, the Siberian subaerial realm may be subdivided into two provinces based on the palaeoclimate conditions prevailing during the Late Pleistocene. These climatic provinces remain in the modern climate.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен